Catalytic Oxidation of 2-Amino-3-Sulfhydryl Propanoic Acid (ASPA) by 2,6- Dicarboxypyridinium Fluorochromate (DCPFC) : A Kinetic and Mechanistic Study: Life Sciences-Amino Acid Oxidation - Mohanapriyaa, S.; Dharmaraja, J.; Raj, V.; Kumaresand, V. (International Journal of Life Science and Pharma Research, 2022)
2-(Pyridin-2-yl) pyridine catalyzed oxidation of 2-amino-3-sulfhydryl propanoic acid (ASPA) by 2,6- DicarboxyPyridinium Fluoro Chromate (DCPFC) has been carried out at 308 K. This amino acid oxidation leads to the formation of a product. Main objective of our present investigation is, Kinetic Oxidation reaction is carried out, from this, reaction rate law, rate equation, mechanisms and rate constant values were measured. Various factors such as Oxidant, Substrate, Acid, Solvent, Catalyst, MnSO4, Acrylonitrile, and NaClO4 influence the reaction rate. This kind of systematic kinetic work explores the physical characterization of the reacting Species. This catalyzed reaction exhibits first order dependence, with respect to [DCPFC] and fractional order with respect to [ASPA], [H+] and 2-(pyridin-2-yl)pyridine. The above reaction is carried out at methane carboxylic acid-water medium. Rate of the reaction has been influenced by varying the percentage of methane carboxylic acid. Addition of NaClO4 appreciably decreases the rate of the reaction. Addition of acrylonitrile does not influence the rate of the reactions, which rules out the polymerization reaction indicating the lack of a free radical pathway. Slight increase in the rate values occur by the addition of MnSO4, which implies that, slight catalytic behaviour of Mn2+ on Oxidation reaction. The reaction described above was carried out at four different temperatures to determine, thermodynamic parameters such as enthalpy and entropy of activation. The appropriate mechanism has been suggested based on the observed data. Our Aim is to find out the reaction mechanism pathway, Order of the reaction by means of various effects such as Oxidant effect, Solvent & Catalyst Effect, etc.,. The product analysis has been confirmed by IR spectral studies and derivative test.